OPTIMALISASI STATUS KESEHATAN REMAJA MELALUI PELATIHAAN KADER REMAJA PEDULI KESEHATAN - Furqan Syakban Nurrahman; Yunie Armiyati (Universitas Muhammadiyah Semarang, 2017)
Various adolescent health problems can reduce the quality of adolescents. Efforts to maintain adolescent health to prepare for a healthy adult physical and mental andproductive needs to be done. Attention to adolescents is one key to the success ofhealth programs. Community empowerment becomes a solution that can enableadolescent to take an active role in public health. Activities in the form of CommunityEmpowerment Program involving adolescents aims to optimize the health status ofadolescents in Kembangarum, Semarang. Adolescent empowerment was conductedthrough the formation of integrated teen service posts, recruitment of adolescenthealth cadres, training of adolescent cadres providing supporting infrastructure andhealth promotion media and counseling post for adolescents. The result of actifitiesshoed there was an increase of cadre knowledge and skill in managing adolescenthealth problem and increasing of adolescent visit to Posyandu. Keywords: Health Status, Teenagers, Cadres, Training